New records of Bartonella in deer keds in Lithuania - Morkutė, Kamilė; Paulauskas, Algimantas; Ražanskė, Irma; Radzijevskaja, Jana (2017)
Bartonella genus contains more than 30 different species of gram-negative intracellular bacteria that infect a wide variety of mammalian hosts. Many different species of hematophagous arthropods, including deer keds, have been confirmed as important vectors in Bartonella transmission. This study represents the first record of deer keds from cervids with presence of Bartonella pathogens in Lithuania. Taxonomic identification of deer keds was based on description of morphological characteristics of pupae and adults and sequence analysis of mitochondrial COI gene. Our investigation demonstrates that in Lithuania cervids are infested with two different species of deer keds Lipoptena cervi and L. fortisetosa. The highest infestation rate was detected in moose (Alces alces). Nested PCR was used to amplify 16S-23S rRNA intergenic spacer region (ITS) of Bartonella genus. Bartonella DNA was detected in both species of deer keds with high prevalence. Sequence analysis of ITS region showed close similarity of detected pathogens to Bartonella schoenbuchensis.